Yearbook of international religious demography / Brill 2017 - Grim, Brian J.; Johnson, Todd M. (Yearbook of international religious demography, 2017)
"The Yearbook of International Religious Demography' presents an annual snapshot of the state of religious statistics around the world. Every year large amounts of data are collected through censuses, surveys, polls, religious communities, scholars, and a host of other sources. These data are collated and analyzed by research centers and scholars around the world. Large amounts of data appear in analyzed form in the World Religion Database (Brill), aiming at a researcher's audience. The Yearbook presents data in sets of tables and scholarly articles spanning social science, demography, history, and geography. Each issue offers findings, sources, methods, and implications surrounding international religious demography. Each year an assessment is made of new data made available since the previous issue of the yearbook. 0The 2017 volume features a wide range of subjects, including religious demography in Botswana, Protestantism in Guatemala, life satisfaction in Japan, fertility rates in the West Bank and Gaza Strip, and the movement of Muslims from the Middle East to Europe."--Back cover